2014
DOI: 10.1007/s10266-014-0175-0
|View full text |Cite
|
Sign up to set email alerts
|

Angioleiomyoma of the tongue: a case report and review of the literature

Abstract: Angioleiomyoma (AL) is a benign tumor derived from smooth muscle. The overwhelming majority of ALs occur in the uterus, gastrointestinal tract, or skin; AL of the oral cavity is infrequent, and AL of the tongue is particularly rare. The present report describes a case of AL of the tongue that resulted in a good outcome. We also review the literature with a special emphasis on the etiology of ALs. It is generally agreed that minor trauma, venous stasis, and hormonal changes are etiological factors for AL. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 11 publications
(19 reference statements)
0
19
0
5
Order By: Relevance
“…9 These tumors appear to arise from the tunica media of small vessels, from arteriovenous anastomoses, or the smooth muscle cells of the circumvallate papillae of the tongue. 5,12 Although the lips are described as the most common site of angioleiomyomas within the oral cavity, [4][5][6] according to reports in the specialized literature published over the last 5 years (summarized in Table 2), the gingiva was the most common anatomical site in 29.4% of cases.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…9 These tumors appear to arise from the tunica media of small vessels, from arteriovenous anastomoses, or the smooth muscle cells of the circumvallate papillae of the tongue. 5,12 Although the lips are described as the most common site of angioleiomyomas within the oral cavity, [4][5][6] according to reports in the specialized literature published over the last 5 years (summarized in Table 2), the gingiva was the most common anatomical site in 29.4% of cases.…”
mentioning
confidence: 99%
“…5,11,12 The most indicated treatment is conservative surgical excision. 6,13 The aim of this study was to describe the clinical, morphological, and immunohistochemical findings of a case of oral angioleiomyoma and compare them with findings described in case reports published during the last 5 years in the specialized scientific literature, identified using the PubMed database.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some reports indicate that angioleiomyoma represents 3.3-9% of tumors in the oral cavity. Ishikawa et al found that the most frequently involved sites in the oral cavity were the lip (48.6%), palate (21.1%), buccal mucosa (9.2%), tongue (9.2%), mandible (8.3%), buccal sulcus (0.9%), labial sulcus (0.9%), mouth floor (0.9%), and gingiva (0.9%) (2). Age at onset ranges from 1 month to 84 years, although most patients are 30 years of age or older.…”
Section: Discussionmentioning
confidence: 99%